HAKIKAT DAN TUJUAN DAKWAH DALAM MEWUJUDKAN KEHIDUPAN YANG DAMAI DAN HARMONIS - Shohib Shohib (Tatar Pasundan: Jurnal Diklat Keagamaan, 2018)
Da'wah is an attempt to change the situation to a better and perfect situation according to Islamic teachings both to the person and society. With other phrases da'wah is an attempt of the faithful to realize Islam in terms of life both to individuals, families, society. Da'wah is the actualization of faith and duties and sacred duties of every Muslim according to their capacity and capability respectively as the embodiment of Islam rahmatan lil alamin.Melalui search related literature on da'wah, this paper discusses the nature and purpose of Islamic da'wah.  Key words : Da'wah, Obligations, Rahmatan lil alamin